Childhood emotional abuse and cyberbullying perpetration among Chinese university students: The chain mediating effects of self-esteem and problematic social media use - Xu, Wei; Zheng, Shujie (Frontiers in Psychology, 2022)
Childhood abuse has been shown to have a range of adverse physical and psychological consequences, including aggression and bullying. While researchers have explored the relationship between childhood abuse and cyberbullying, little is known about the impact of emotional abuse on cyberbullying. This study examined the link between childhood emotional abuse (CEA) and cyberbullying perpetration among university students in the Chinese cultural context, as well as the chain mediating effect of self esteem and problematic social media use (PSMU). A total of 835 university students (18–25 years old; 293 males, 542 females; Mage = 19.44 years, SD = 1.28) completed the Childhood Trauma Questionnaire Short-Form (CTQ-SF), Rosenberg Self Esteem Scale (RSES), the Social Media Use Questionnaire (SMUQ) and Cyberbullying Inventory (CBI). The results showed that CEA and PSMU were positively correlated with cyberbullying, self esteem was negatively correlated with cyberbullying. Besides, self-esteem and PSMU sequentially mediated the relationship between CEA and cyberbullying perpetration.